Subjective and objective indicators of racial progress - Betsey Stevenson; Justin Wolfers (Institute for the Study of Labor (IZA), 2013)
Progress in closing differences in many objective outcomes for blacks relative to whites has slowed, and even worsened, over the past three decades. However, over this period the racial gap in well-being has shrunk. In the early 1970s data revealed much lower levels of subjective well-being among blacks relative to whites. Investigating various measures of well-being, we find that the well-being of blacks has increased both absolutely and relative to that of whites. While a racial gap in well-being remains, two-fifths of the gap has closed and these gains have occurred despite little progress in closing other racial gaps such as those in income, employment, and education. Much of the current racial gap in well-being can be explained by differences in the objective conditions of the lives of black and white Americans. Thus making further progress will likely require progress in closing racial gaps in objective circumstances.
Keywords: D6; I32; J1; J7; K1; 330; subjective well-being; life satisfaction; happiness; race